2010
DOI: 10.5860/crl-34r2
|View full text |Cite
|
Sign up to set email alerts
|

Information-Seeking Behavior in the Digital Age: A Multidisciplinary Study of Academic Researchers

Abstract: This article focuses on how electronic information resources influence the information-seeking process in the social sciences and humanities. It examines the information-seeking behavior of scholars in these fields, and extends the David Ellis model of information-seeking behavior for social scientists, which includes six characteristics: starting, chaining, browsing, differentiating, monitoring, and extracting. The study was conducted at Tennessee State University (TSU). Thirty active social sciences and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 13 publications
2
44
0
1
Order By: Relevance
“…Niu and Hemminger (2012) found academic status to be an important issue in information seeking behaviour for faculty members, students and staff at five US universities. Interviewing scholars in the field of humanities, Ge (2010) revealed that PhD students and assistant professors use electronic resources more than associate professors and professors. Jamali and Nicholas (2006) found that PhD students browse electronic journals more than senior scholars in physics and astronomy.…”
Section: Professions and Sciencementioning
confidence: 99%
“…Niu and Hemminger (2012) found academic status to be an important issue in information seeking behaviour for faculty members, students and staff at five US universities. Interviewing scholars in the field of humanities, Ge (2010) revealed that PhD students and assistant professors use electronic resources more than associate professors and professors. Jamali and Nicholas (2006) found that PhD students browse electronic journals more than senior scholars in physics and astronomy.…”
Section: Professions and Sciencementioning
confidence: 99%
“…[11][12][13][14][15] Increasing availability of electronic articles, including backfiles, through libraries has been responsible for the largest percentage of the increase of e-article readings in the United States and elsewhere. 8,9 Therefore, libraries and publishers are both reacting to user preferences and driving changes in behaviour by changing to e-formats.…”
Section: Background and Research Questionsmentioning
confidence: 99%
“…I also showed them Meho and Tibbo's (2003) extended model of accessing information, networking for information, verifying the data, and managing large sets of information effectively. Like other researchers who elicited feedback from American faculty on this model (Ge 2010;Shen 2013), I found that having Atameken University faculty comment on a specific model expanded our conversation on research in useful ways. As the section below demonstrates, much of these faculty members' information-seeking practices are similar to that seen in other regions; in the following section, I will highlight some of the contextual differences emerging from a location in Kazakhstan.…”
Section: Assessing Ellis's 1989 Information-seeking Modelmentioning
confidence: 95%